Digitising Folktales for Animation and Value Education - Animated Video 6 - Yusuff, Ayodele; Eleshin, Abisoye (Regenerating Non-Formal Learning in Africa: Digitizing Yoruba Folktales for Animation and Value Education, 2023)
Animation of folktales
Keywords: Learning; Animation (Cinematography); Children; Child psychology; Curriculum planning; African Studies; Tortoise